Analysis of The Distribution of Geothermal Potential and The Manifestations in Ijen Volcanic Complex Based on Land Surface Temperature and Geomorphology - Bowo Eko Cahyono; Nurfaizatul Jannah; Agus Suprianto (Natural B, Journal of Health and Environmental Sciences, 2019)
Indonesia's geographical conditions which are at the confluence of three tectonic plates contribute to the availability of geothermal energy. The first step that can be taken in geothermal potential exploration activities is to study the characteristics of geothermal potential areas. In this case the study of the characteristics of geothermal potential will be carried out in the Ijen Mountains complex. This study aims to analyze the distribution of geothermal potential based on land surface temperature, and geothermal manifestations based on the association of land surface temperature and geomorphology. Remote sensing data used in the study were Landsat 8 images acquired in September 2013, 2015, and 2017. The results showed that geothermal potential areas were in the interior of the Ijen Mountains caldera with a temperature anomaly of 26-50 °C which was dominated by high greenish vegetation. While some geothermal manifestations that have been recorded are known to be associated with lineament that intersects with high land surface temperatures, so that the lineament that has the potential to be a fluid discharge pathway for geothermal manifestations is lineament that consistently intersects with high land surface temperatures in September 2013, 2015, and 2017 with the Southeast-Northwest and Southwest-Northeast orientations.